The Role Of The Match Office In Matching As A Marriage Needs Agent - Muhammad Maymun (Indonesian Academy of Social and Religious Research (IASRR), 2022)
This paper aims to explain the role of Rumaysho's matchmaking agency in helping the public in choosing their soul mate. This writing method is a qualitative research with a socio-normative approach. Rumaysho's matchmaking agency was established as a da'wah institution and helped the community in finding their soul mate. The role of the Rumasyho matchmaking agency is not only to find but to guide potential partners to marriage. Many people in the modern era have become less confident in choosing a mate, so the alternative is to come to the Rumasyho matchmaking bureau to register themselves.